Post-Pandemic Evaluation of Emergency Medicine Workforce Stability - Chaudhary, Fihr; Agrawal, Devendra K. (Archives of Clinical and Medical Case Reports, 2026)
Physician workforce projections in emergency medicine were developed in the year 2020 based on the assumptions and baseline data during the unprecedented disruption in healthcare delivery due to COVID-19 pandemic. However, the fundamental assumptions in this project might not be realistic in the post COVID-19 era. In this article, the accuracy of 2020 emergency medicine workforce oversupply projection was critically evaluated and comprehensively reassessed considering post COVID-19 data. The findings support the underestimation of the demand and exaggeration of projected physician surplus. The post-pandemic trends suggest a more fragile emergency medicine workforce marked by sustained attrition and vulnerability to stressors. A stable or modest increase in the demand for emergency physicians between the years 2030 and 2040 is projected. The findings suggest that clinical workload per physician is likely to increase due to the emergency care of aging population, delayed presentations of acute and chronic diseases, and increased boarding and throughput challenges. Accordingly future workforce projections must incorporate updated attrition estimates and account for structural shifts in emergency care delivery. This would require maintaining or expanding demand for emergency physicians in next decade and beyond.